Implementasi Program Keluarga Harapan dalam Pemberdayaan Masyarakat Miskin di Kelurahan Tatura Selatan Kecamatan Palu Selatan Kota Palu - Akmala, Wanda; Adam, Adam; Munir, Nurasia (Journal of Islamic Community and Development, 2026)
This study aims to analyze the implementation of Program Keluarga Harapan (PKH), Indonesia's conditional cash transfer program, in empowering poor communities in South Tatura Village, South Palu District, Palu City, and to identify the factors influencing its implementation. The study employed a qualitative approach using primary data collected through interviews and secondary data obtained from books, documents, reports, legislation, and other relevant sources. Data were collected through interviews, observation, and documentation. The research informants consisted of the Village Head, PKH facilitators, and 10 PKH beneficiary families. The findings indicate that the implementation of PKH has been carried out gradually in accordance with the program guidelines, including the identification of target households, the distribution of conditional cash assistance, and mentoring for beneficiaries. The program has had positive impacts, including improved access to health and education services, enhanced household skills in resource management, and positive changes in the socio-economic behavior of the community. The study also suggests that updating the data of prospective Beneficiary Families (KPM) should be optimized through direct field verification by PKH facilitators to ensure that program participants genuinely meet the established eligibility criteria.